PENGAWASAN IZIN TRAYEK ANGKUTAN UMUM WAWONASA DI DINAS PERHUBUNGAN KOTA MANADO - MANAMBE, SELISA; RURU, JOORIE MARHAEN; TAMPONGANGOY, DEYSI LIVI (JURNAL ADMINISTRASI PUBLIK, 2018)
This research aims to know the supervision of public transport route permits wawonasa Transport Service inthe City of Manado. Research methods used in this research is descriptive qualitative theory of supervisionaccording to M. Manullang (2004). Teknik data collection is done by means of an interview anddocumentation, data obtained from a variety of sources with data reduction steps, the presentation of data,and the withdrawal of the conclusion. The results showed that the supervision of the Department oftransportation in overseeing public transport route permit on wawonasa it's been quite effective, held threetimes each month supervision. But still lack of assertiveness from the Department of transportation the city ofManado in the sanction every owner/drivers of public transportation does not extend permission late/theroutes of the vehicle, so there are still many vehicles ditilang at the moment there are inspection/supervision.As well as the responsibility of the owners of public service vehicles still less in pay/extend permission topublic vehicles owned trackage, it can reduce the income from the revenue of the original area.Keywords: Supervision, Permits The Routes Of Public Transport